The Irish Experience in Ontario: Rural or Urban? - Nicolson, Murray (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1985)
The purpose of this paper is to respond to several new theories which, if accepted, could alter the historical perception of the role played by urban centres in the adjustment of Irish Catholics in nineteenth century Ontario. Donald Akenson, a rural historian, believes that the Canadian experience of Irish immigrants is not comparable to the American one. Akenson contends that the numerical dominance of Protestants within the national group and the rural basis of the Irish community, negated the formation of urban ghettos and allowed for a relative ease in social mobility. In comparison the American Irish were dominantly Catholic urban dwelling and ghettoized. In addition the new labour historians believe that the rise of the Knights of Labor caused the Orange and Catholic Irish in Toronto to resolve their generational hatred and set about to form a common working-class culture. This theory must presume that Irish Catholic culture was of little value to be rejected with such ease. The writer contends that neither theory is valid. In the ghettos of Toronto the fusion of an Irish peasant culture with traditional Catholism produced a new, urban, ethno-religious vehicle — Irish Tridentine Catholism. This culture, spread from the city to the hinterland and, by means of metropolitan linkage, throughout Ontario. Privatism created a closed Irish society, one they were born into and left when they died. Irish Catholics co-operated in labour organizations for the sake of their family's future, but never shared in the development of a new working-class culture with their old Orange enemies.